2003
DOI: 10.1063/1.1599961
|View full text |Cite
|
Sign up to set email alerts
|

Formation energy of Stone–Wales defects in carbon nanotubes

Abstract: A Stone-Wales ͑SW͒ defect is a dipole of 5-7 ring pair in a hexagonal network, which is one of the most important defective structures in carbon nanotubes ͑CNTs͒ that will affect mechanical, chemical, and electronic properties of CNTs. Using the extended Hückel method, we calculated the formation energy of SW defects in carbon nanotubes. The formation energy of SW defects was then fitted to a simple formula as a function of the tube radius and the orientation of a SW defect in the tube. This result provides a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(113 citation statements)
references
References 14 publications
10
98
1
4
Order By: Relevance
“…Using the PBE96-GGA instead of the LDA predicts that the barrier to eliminate a Stone-Wales defect is slightly smaller, making the estimated temperature for onset of annealing lower by about 50 K than it is with the LDA. Previous studies have found broadly similar results [44,[132][133][134][135][136][137][138], with one exception [139]. The exception (Kaxiras and Pandey) uses a model based on rhombohedral graphite instead of a single graphene sheet, which all the others use, and gives significantly higher values for the formation and activation energies.…”
Section: Displacement Defectssupporting
confidence: 62%
“…Using the PBE96-GGA instead of the LDA predicts that the barrier to eliminate a Stone-Wales defect is slightly smaller, making the estimated temperature for onset of annealing lower by about 50 K than it is with the LDA. Previous studies have found broadly similar results [44,[132][133][134][135][136][137][138], with one exception [139]. The exception (Kaxiras and Pandey) uses a model based on rhombohedral graphite instead of a single graphene sheet, which all the others use, and gives significantly higher values for the formation and activation energies.…”
Section: Displacement Defectssupporting
confidence: 62%
“…[325][326][327] The formation energy of SW defects proved to be dependent on the tube diameter and chirality, [328][329][330] analogously to other point defects. Overall, MD simulations showed that the concentration of SW defects after impact of energetic ions 174,175,178,265 and electrons 210 is much smaller than those for adatoms and interstitials.…”
Section: Stone-wales Defectsmentioning
confidence: 99%
“…It is well known that the generation of an SW defect consumes about 5 eV to eject a knock-on carbon atom from the honeycomb lattice, 13,14 where the transferred energy is almost identical to the approximate 80 keV for the perpendicularly irradiated electron beam. However, the electron energy that induced the tube shrinkage was much smaller than the threshold value, and the largest shrinkage rate was observed at 1 keV in this experiment.…”
Section: Resultsmentioning
confidence: 99%
“…10 It is well known that high energy electron irradiation induces a variety of structural changes in carbon nanotubes; perpendicularly incident electrons induce lateral ejection of carbon atoms; thus creating Stone-Wales (SW) defects on the honeycomb lattice. [11][12][13][14][15][16] The threshold energy needed to induce this so-called "knock-on mechanism" is about 86 keV, 11 and the propagation of the SW defect plays an essential role in many structural transformations, 13 because a heptagonheptagon combination cannot sustain the initial flat surface but instead generates a local curvature. Therefore, SW defects combined with local excitation of the carbon bond induces a variety of carbon nanostructures 11,[17][18][19][20][21] including the creation of fullerenes from carbon soot, 17 lattice destruction into amorphous carbon, 11,18 nanotube scissoring, 19 and the cross-linking of nanotubes and fullerenes.…”
Section: Introductionmentioning
confidence: 99%